2022
DOI: 10.3390/tropicalmed7080145
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection with Plasmodium vivax and COVID-19 in Thailand

Abstract: With the emergence of SARS-CoV-2, healthcare systems not only had to address the pressing clinical needs of the COVID-19 pandemic but anticipate the effect on and of other conditions and diseases. This was of particular concern in areas of the world endemic with malaria, a disease which takes hundreds of thousands of lives each year. This case report from Thailand describes a 25-year-old man diagnosed with Plasmodium vivax, who was then found to be co-infected with COVID-19. Both conditions can have overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…To obtain the stochastic basic reproduction number, we consider the co-infected class of stochastic model (4).…”
Section: Basic Reproduction Number For Malaria-covid-19 Co-infection ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the stochastic basic reproduction number, we consider the co-infected class of stochastic model (4).…”
Section: Basic Reproduction Number For Malaria-covid-19 Co-infection ...mentioning
confidence: 99%
“…There are several studies that have done on co-dynamics of COVID-19 including TB [23], Dengue [33], Cholera [16] as well as co-dynamics of Malaria, see, e.g. [1,31,4]. Malaria and COVID-19 diseases have affected millions of people globally, and much more in tropical countries, where the emergence of COVID-19 has increased the burden of diagnosis and treatment of malaria [30] because of the similarities in presenting symptoms leading to several health challenges [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the available reports about SARS-CoV2 co-infections describe concomitant bacteria, fungus and other viral infections, especially associated with respiratory infections and pneumonia. In depth studies have not been conducted for SARS-CoV2 and protozoan co-infections; however a few reports are available showing co-infections occur with Toxoplasma (Montazeri et al, 2022), Plasmodium (Raham, 2021;Boonyarangka et al, 2022), Babesia (Jacobs and Siddon, 2021), Leishmania (Pikoulas et al, 2022) and Trypanosoma (Alberca et al, 2020). In the first year of the COVID-19 pandemic, worldwide malaria cases increased from 227 million in 2019 to 241 million in 2020 (World Health Organization, 2021) and a high rate of latent T. gondii infection was also found among COVID-19 patients with severe manifestations reported in the Middle East region (Montazeri et al, 2022).…”
Section: The Epidemiology Of Protozoan Parasite-viral Co-infectionsmentioning
confidence: 99%
“…Although recent studies have shown that mosquitoes do not transmit the COVID-19 virus, the COVID-19 global pandemic is hampering mosquito-borne disease control efforts, such as disrupting malaria services (5). This not only increases the risk of mosquito-borne pathogens transmission but also lead to a significant increase in the number of cases and deaths (6,7). According to the statistics of the World Health Organization, more than 700,000 deaths caused by mosquito-borne diseases annually (8).…”
Section: Introductionmentioning
confidence: 99%